The side-effects of antidepressants on sexual function - Kulo?lu, Murat; Atmaca, Murad; Geçici, Ömer; Kiliç, Nülüfer; Tezcan, A. Ertan (My University, 2000)
Objective: Sexual side effects are frequent, causing poor comp-liance and recently being considered as side-effects of antidepressant treatment. In this study, it was aimed to compare sexual side effect profiles of different group antidepressants and to assess the results under literature. Method: The study group consisted of 300 patients (182 females, 118 males) who had applied to diagnosed as mood disorder (n=165), anxiety disorder (n=70), somatoform disorder (n=59) and adjustment disorder (n=6) according to DSM-IV. After the patients have been divided into four groups (n=60/group), each group was given chlorimipramine (mean: 168.2±24.2 mg/day); fluvoxamine (mean: 143.4±16.7 mg/day); sertraline (mean: 114.7±14.4 mg/day); paroxetine (mean: 42.3±3.9 mg//day); and moclobemide (mean 336.8±42.6 mg/day) respectively. All subjects were fulfilled a semistructural form which included sociodemographic, clinical characteristics and sexual function informations including libido, erection-lubrication problems and orgasm problems at the beginning and sexual information part one month later if drug tolerated. Results: Of the patients, 98 had (%32.7) any sexual side effect. Of them, 12 expressed spontanously and 86 (%87.8) by provocation. Decreased libido was the most frequent amongst all side effects. Paroxetine and sertraline reported side effect frequently. Conclusions: Results of our study revealed that sexual side effects were an important problem in front of antidepressant treatment.
Antidepresan i?laçlarin cinsel i?şlev üzerine etkileri
Keywords: Antidepressant treatment; Sexual function; Side-effects